Financial Indicators Shaping Share Price Movement: Insight from the Dhaka Stock Exchange SME Board - Ahammed, Md. Yousuf; Chowdhury, Md. Ariful Haque; Rahman, Md. Tahidur; Tazminur, Shayla (International Journal of Economics and Financial Issues, 2024)
This study intends to explore the parameters that influence the share price movement of companies listed under the SME board on Dhaka Stock Exchange (DSE). The small capital platform, popularly known as the SME board is a specialized to trade share of Small and Medium Sized Enterprises (SMEs). Based on secondary data, the present study used three independent variables, such as Earning Per Share (EPS), Price Earning (P/E) ratio, and Net Asset Value (NAV) per share to evaluate the fluctuations of share price in the market. All the companies listed on the DSE SME board were taken into consideration for the current study. Relevant Data concerning dependent and independent variables were collected from the DSE website. Average closing price of selected shares were collected during March 15, 2022–March 14, 2023. The study performed descriptive statistics, correlation, and regression analysis using Statistical Package for Social science (SPSS) software. The study revealed that the fluctuations of share price of SME companies was significantly influenced by EPS, Net Asset NAV per share, and P/E ratio. This maiden study is expected to have implications to companies intending to be listed, investors, regulators, and other stakeholders in Bangladesh.